2022
DOI: 10.3389/fpubh.2022.855468
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Perspective on Vaccine-Hesitancy at the Beginning of Israel's COVID-19 Vaccination Campaign and Public's Perceptions of Physicians' Knowledge When Recommending the Vaccine to Their Patients: A Cross-Sectional Study

Abstract: Because public healthcare workers (HCWs) are at the forefront of the battle against COVID-19, they must be able to provide vaccination information to their patients and respond to their anxieties and concerns. This research objectives were to (1) examine physicians' perceptions of how they received information about the Pfizer COVID-19 vaccine, their attitudes toward hesitant colleagues, and their own knowledge and self-efficacy in communicating information to their patients, and (2) to examine the public's pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
0
17
0
1
Order By: Relevance
“…In 2005, Poland et al presented several arguments about mandated influenza vaccination that parallel discussions about COVID-19 vaccination today, including the morbidity and transmissibility of influenza, limitations on scheduling coverage for sick workers, the effectiveness of work requirements in increasing vaccination rates, and the ethical and moral duty of healthcare workers [28]. Despite this duty, one study found that family medicine physicians were more motivated by institutional pressures to vaccinate than the hope of providing protection for their patients [29]. It has also been argued that HCW vaccination requirements establish an example of HCWs as leaders in good preventative medicine practices [25].…”
Section: Pre-covid-19 Vaccine Hesitancy Among Healthcare Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, Poland et al presented several arguments about mandated influenza vaccination that parallel discussions about COVID-19 vaccination today, including the morbidity and transmissibility of influenza, limitations on scheduling coverage for sick workers, the effectiveness of work requirements in increasing vaccination rates, and the ethical and moral duty of healthcare workers [28]. Despite this duty, one study found that family medicine physicians were more motivated by institutional pressures to vaccinate than the hope of providing protection for their patients [29]. It has also been argued that HCW vaccination requirements establish an example of HCWs as leaders in good preventative medicine practices [25].…”
Section: Pre-covid-19 Vaccine Hesitancy Among Healthcare Workersmentioning
confidence: 99%
“…Older HCWs would be more amenable to vaccination due to the greater risk for severe disease, whereas younger HCWs may be more hesitant due to greater exposure to social media [84] and may be more prone to risk-taking behaviors [85]. On the other hand, younger HCWs may be more receptive due to more liberal political views compared to older adults [29]. One study noted that older HCWs were more likely to vaccinate across all professions except for physicians, but younger physicians were more likely to vaccinate.…”
Section: Demographics Of Vaccine Hesitant Hcwsmentioning
confidence: 99%
“…On the other hand, if people see that their opinion is not popular, they are more likely to be reserved and silent ( 85 , 86 ). In Israel, this spiral of silence spilled over into many areas, for example among doctors who noted that the system was pressing them to “toe the line” and was intolerant of any expressions of hesitancy ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Varied ‘conspiracy theories’ disseminated among varied populations, resulted in increased vaccine hesitancy and subsequently, a substantial decrease in vaccine uptake [ 19 ]. Additional factors that may have contributed to vaccine hesitancy in Israel were the perceptions that human rights are disregarded, as some sectors (such as teachers and employees of local municipalities) were ‘coerced’ to be vaccinated [ 20 ], or that the medical providers do not as yet have sufficient knowledge concerning the long-term effects of the vaccine [ 21 ].…”
Section: Covid-19 Vaccine Uptakementioning
confidence: 99%